Improving Creative Thinking SkillsThrough Learning Cycle 5E Lessons of Akidah Akhlak at SMP Muhammadiyah 1 Surabaya - Thaariq Achmad Novandra; Aldo Redho Syam; Anita Puji Astutik (Ar-Fachruddin: Pendidikan Agama Islam, 2024)
Research Objective: This study aims to describe the creative thinking skills of students at SMP Muhammadiyah 1 Surabaya, explain the 5E Learning Cycle approach in teaching Aqidah Akhlak, and analyze the improvement of creative thinking skills through this approach in Aqidah Akhlak lessons. Methodology: The research employs a qualitative descriptive method. Data were collected through interviews, field observations, and documentation, then analyzed using data reduction, data display, and conclusion-drawing techniques. Findings: The study found that students' creative thinking skills were initially low before implementing the 5E Learning Cycle approach. After applying this approach, which consists of five stages—engagement, exploration, explanation, elaboration, and evaluation—there was a significant improvement in students' creative thinking skills, including fluency, flexibility, originality, and detail in Aqidah Akhlak lessons. Research Implications/Limitations: This study highlights the importance of implementing the 5E Learning Cycle approach to enhance students' creative thinking skills. However, the study is limited to the context of SMP Muhammadiyah 1 Surabaya and requires further validation in different educational settings for broader generalization. Originality/Value: This research provides a novel contribution by demonstrating that the 5E Learning Cycle approach can be an effective method for developing students' creative thinking skills in Aqidah Akhlak lessons. It is highly relevant to support 21st-century educational needs, which emphasize higher-order thinking skills.